PRASASTI "Peningkatan Remaja Sehat tanpa Seks Bebas dan Kehamilan tidak Diinginkan" - Maulida Fatmah; Fatima Azzahra Herlianty; Zahra Pramesti; Dini Safitri; Azizah Maulana; Romdiyah (CATHA SAINTIFICA, 2026)
Adolescence is a crucial transition phase vulnerable to risky behaviors such as free sex, which can lead to Sexually Transmitted Infections (STIs) and Unwanted Pregnancies (KTD). This study aims to develop the PRASASTI application and evaluate adolescents' understanding of reproductive health, STIs, and prevention of risky sexual behavior. This study contributes by developing PRASASTI, a digital educational application designed to improve adolescents' literacy regarding reproductive health and the prevention of risky sexual behavior. The research method used was Research and Development (R&D) through the stages of need analysis, design, development, validation, and limited trial, involving 24 IPPNU adolescent respondents in Bogelan Village, Wonosobo. Data were collected using a structured true-false questionnaire and analyzed descriptively using percentage distribution. The results showed that most respondents had a very high level of knowledge: 100% correctly identified STI types, PMS symptoms, and the psychological impact of free sex, while understanding of puberty, HIV transmission, and the physical impact of STIs reached above 85%. In conclusion, PRASASTI is useful as adolescent-friendly educational media that can support reproductive health literacy, strengthen prevention of risky sexual behavior, and encourage healthier decision-making among adolescents